MARKET OF HOTEL SERVICES IN UKRAINE: ASSESSMENT OF THE CURRENT STATE AND DEVELOPMENT DYNAMICS - Yudina, O. I.; КоrneyevМ. V.; Stebliuk, N. F.; RazinkovaМ. Yu.; Mishina, Ye. S. (Systems and Technologies, 2023)
The article examines the current state and dynamics of the development of the hotel services market in Ukraine by determining the peculiarities of the change in statistical parameters characterizing the activity of business entities in the field of hospitality. The main goal of this article is to analyze the market of hotel services in Ukraine, to assess its current state and development trends based on the dynamics of performance indicators of collective accommodation facilities. In the work, by conducting a quantitative analysis of the data of the State Statistics Service of Ukraine, the current state of the market of hotel services in the country, its structure, features and development trends is characterized, taking into account the classification of types of economic activity according to KVED-2010. By interpreting the indicators of the number of hotels and similar accommodation facilities, persons staying in collective accommodation facilities, employed workers in the hotel sector, and the volume of implementation and production of hotel services, trends in their development in Ukraine were established. So, based on the assessment of the dynamics of these statistical indicators, negative trends in their development in Ukraine in the last three years have been established, which is explained by the negative impact of the COVID-19 pandemic, political and economic crisis phenomena in the country and the world. In the course of the research, it was determined that Odesa, Zakarpattia, Lviv, and Kyiv regions have the largest number of hotels and similar accommodation facilities, and, accordingly, greater profit from this activity. The growth of the role of individual entrepreneurs in the hotel industry and the directions of their cooperation with hotel chains, which involve the pooling of resources, knowledge and innovative activity of FOPs to create new consumer offers, have also been established. The growth of the share of FOPs in the structure of business entities in the hotel services market is explained by the simple procedure of their registration, lower costs of business management, greater productivity and efficiency of service implementation, flexibility in decision-making, provision of innovative services and introduction of new concepts, as well as the need to ensure self employment.